(untitled) (Lex localis - Journal of Local Self-Government, 2019)
Few studies have been conducted to analyze influential factors of state user charge reliance. This study empirically examines the impact of interstate competition and fiscal rules on state user charge reliance between 1991 and 2014 by applying panel data analysis. Also, this study aims to investigate mechanisms of state user charge reliance and various variables related to user charge reliance, which enhances and broadens understanding of factors that affect state user charge reliance. According to this analysis, overall state user charge reliance is mainly explained by interstate competition, fiscal rules, state tax effort, ideological standpoint and income level. Practically, states need to attend to their taxable resources and consider the actual effect of TELs and balanced budget rules in limiting the growth of government. Future research is recommended to examine mechanisms of state specific user charge sources and expand the variables related to user charge reliance.